Populasi Bakteri Tanah pada Padi Pasang Surut dengan Aplikasi Pupuk Cair Neptunia Prostrata - Dila Aksani; Siti Nurul Aidil Fitri; Siti Masreah Bernas (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2016)
Aksani, et al. Soil Bacteria Population in Paddy Tidal Land by Application of Liquid Fertilizer Neptunia prostrata. JLSO 5(2):170-177.Â High soil acidity in tidal lowland influences soil bacteria population. This research aimed to determine soil bacteria population with liquid fertilizer application made by Neptunia prostrata for paddy grown in tidal lowland. This research using factorial completely randomized design with two factors and three replications. The first factor was liquid fertilizer rate, consisting of three levels: 96 mL pot-1(P1), 120 mL pot-1(P2) and 144mL pot-1(P3). The second factor was application period consisting of three times: once time at the planting time (W1), two times at the planting time and harvesting time and three times at the planting time, primordial stage and harvesting time. The result showed that the highest soil bacteria population was 10,94 log spk g-1with the treatment of Â 144 mL pot-1Â liquid fertilizer and given once time at the planting time (P1).